WEANING TO ESTRUS INTERVAL OF SOWS REARED UNDER FIELD CONDITION OF AIZAWL - LALREMRUATA, C.; HMAR, L. (Indian Journal of Animal Production and Management, 2017)
ABSTRACTA total of 29 sows (14 LWY, 7 HS and 9 BB) sows were studied for a period of 11months under the field condition of Aizawl district, Mizoram. The average weaning to estrusinterval (WEI) of sows was found to be 13.52±3.35 days. The WEI in Large White Yorkshire,Hampshire and Burmese Black was found to be 17.43±6.24, 7.67±0.49 and 12.00±5.21 daysrespectively. However, there was non-significant difference among the three breeds i.e LargeWhite Yorkshire (LWY), Hampshire (HS) and Burmese Black (BB).Key words : Weaning to estrus interval, sows, field condition.